2020
DOI: 10.1021/acs.jpcb.0c06666
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phonon Density of States from Constant-Pressure Heat Capacity Data of Soft Organic Materials in the Glassy and Crystalline States by Using the Real-Coded Genetic Algorithm

Abstract: A method was proposed to derive the phonon density [g(ω)] of states of materials from their heat capacity data by using Real-Coded Genetic Algorithm (RCGA) with Just Generation Gap + Real-Coded Ensemble Crossover. The performance of the method was confirmed by testing whether or not the RCGA reproduces a reasonable g(ω) by analyzing the set of heat capacity data evaluated from an initially assumed model g 0 (ω) composed of Debye and optical modes. As an example, constantpressure heat capacities (C P s) were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 28 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…This roughly agrees with that of 3/4 = 0.75 evaluated from the results of spectroscopic measurements. In view that the value in the range 0.7–0.75 is a relatively small fraction of the whole degrees of freedom below ω = 400 K, the flat distribution of g (ω) potentially reflects the following situation: previously, we carried out model analyses which tried reproducing g (ω) using the RCGA from the sets of the heat capacity data computed from the assumed g 0 (ω) distributions involving two optical phonon modes and reported that the optical phonon in the high-frequency side in g (ω) became much broadened to have a wide distribution compared with that assumed in the initial g 0 (ω) . The reason remaining unclear, it is desired to develop the RCGA analysis in future without such a broadening effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This roughly agrees with that of 3/4 = 0.75 evaluated from the results of spectroscopic measurements. In view that the value in the range 0.7–0.75 is a relatively small fraction of the whole degrees of freedom below ω = 400 K, the flat distribution of g (ω) potentially reflects the following situation: previously, we carried out model analyses which tried reproducing g (ω) using the RCGA from the sets of the heat capacity data computed from the assumed g 0 (ω) distributions involving two optical phonon modes and reported that the optical phonon in the high-frequency side in g (ω) became much broadened to have a wide distribution compared with that assumed in the initial g 0 (ω) . The reason remaining unclear, it is desired to develop the RCGA analysis in future without such a broadening effect.…”
Section: Discussionmentioning
confidence: 99%
“…g (ω) derived from each set of C P data for BA h and BA d crystals was optimized using the RCGA with just generation gap (JGG) + real-coded ensemble cross-over (REX) method, , as reported previously . To calculate with a computer, the numerical integration in eq was replaced with summation, as given in eq , where Δω, being a digitization unit regarding ω, was taken to be 3 K. A set of candidate parameters for solutions, represented as a genotype in GA, is an array of real numbers with n length, and the REX­( n + k ) is a multiparental cross-over model, where n + k denotes the number of parents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations